Determining the Delayed Effects of COVID-19 in Children Hospitalized in Southeastern Iran from 2021 to 2023 - Groohi-Sardou, Shima; Dehghani, Mohammad Mahdi; Raesi, Rasoul; Hushmandi, Kiavash; Daneshi, Salman (Current Pediatric Reviews, 2025)
<span class=
Keywords: Delayed complications